Uma Leitura Republicana Do Discurso Da Servidão Voluntária A Partir Dos Exempla - Nascimento, Andre Manoel Do [UNIFESP] (2018)
The Aim Of This Dissertation Is To Present A Reading Of The Discourse Of Voluntary Servitude That Starts From Its Constitution As A Rhetorical Discourse, Especially Of The Exempla, To Link This Text To The Tradition Of Italian Republicanism. There Are Many Examples Used By La Boétie, Of Which We Highlight Those Referring To Cities Historically Recognized As Republican. Therefore, We Work As A Primary Reference The Three Essays That Accompany The Brazilian Edition Of The Discourse, Those Of Pierre Clastres, Claude Lefort And Marilena Chauí. From These Three Comments The Rhetorical Questions And The Efforts To Demonstrate The Historical Motivation Of La Boetie's Discourse Were Emphasized, And Readings Were Made That Sought To Problematize Such Themes By Showing The Relations That Existed Between The Contr'un And Theoretical And Practical Questions Of Your Time. Finally, We Sought To Demonstrate The Similarities Between Italian Republicanism Themes - Such As The Rule Of Law, Caesar's Condemnation, The Search For